PERMASALAHAN TKI DI LUAR NEGERI DAN SEJENISNYA - Tetty Marlina Tarigan (Journal of Gender and Social Inclusion in Muslim Societies, 2020)
A series of government policies that are deemed incapable of changing the welfare of society, especially those of low economic groups, there are other sectors of work that are promising enough to change their fate to be more prosperous, namely as Indonesian Workers (TKI). This effort received a good response from the community where people have their own reasons which are considered not excessive considering that the promised salaries are quite large when compared to the wages they receive as laborers in Indonesia. The placement of migrant workers abroad also has a negative effect, with cases that befell TKI both before, during work and when they return to their home areas in Indonesia. Of the many problems, at least the problem of education is one of the factors in the process of violence against TKI. On the other hand, the closure and restrictions on sending TKI through formal programs can stimulate the development of various forms of illegal sending, either through taikong / labor brokers or other informal channels. The problem of Indonesian migrant workers abroad also still affects the conditions of Indonesian labor, especially in relation to the implementation, placement and protection of Indonesian workers abroad. Various policies regarding the sending of TKI still need to be improved and perfected so that TKI can work well, are protected by their human rights and can fully enjoy the results of their hard work. In addition, the safety of TKI who work abroad has not received optimal protection.